Effect of Myelopathy on Outcomes After Cervical Disc Replacement: A Study of a Local Patient Cohort and a Large National Cohort. (1st September 2019) - Qureshi, Sheeraz; Samuel, Andre; Mcanany, Steven; Iyer, Sravisht; Albert, Todd; Gang, Catherine
Abstract: INTRODUCTION: Previous research has shown increased perioperative morbidity after anterior cervical discectomy and fusion (ACDF) for patients with myelopathy. However, the association of myelopathy with outcomes after CDR has not yet been shown. METHODS: Consecutive patients undergoing CDR by a single surgeon were identified and patients undergoing CDR in the 2015 and 2016 National Surgical Quality Improvement Program (NSQIP) database were identified. Patients with a preoperative diagnosis of cervical myelopathy were identified in both cohort, and perioperative outcomes and short-term postoperative outcomes were compared between patients with and without myelopathy. Comparisons were also controlled based on the number of levels treated. RESULTS: A total of 27 patients were identified in the institutional cohort, 12 patients (44.4%) with myelopathy. A total of 3023 patients were identified in the national cohort, 411 (13%) with myelopathy. In the institutional cohort, the nonmyelopathy group saw significant improvements in neck disability index (NDI), and visual analog scale (VAS) neck and arm pain at both 2 and 6 wk postoperatively. The myelopathy group only saw a significant improvement in NDI at 6 wk (−13.1± 4.1, P  < .05) but not at 2 wk ( P  > .05). In the national cohort, myelopathy was associated with longer operative time and length of stay, even after controlling for the number of levels treated ( P  < .05). However, there was no significant difference in perioperative complications ( P  > .05). CONCLUSION: Myelopathy is not associated with increased perioperative morbidity and complications after CDR. Significant improvement in patient reported outcomes is seen at 6 wk in myelopathy patients, although more rapid improvement is seen in patients without myelopathy.